Air-conditioning guidelines for healthcare facilities during the covid pandemic - Dr. Ashutosh Sharma; Dr. Ramesh Kumar K; Dr. Saroj K Patnaik (International Journal of Medical Research and Review, 2021)
Coronavirus disease (COVID-19) is an infectious disease caused by a newly discovered Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The disease spreads primarily through respiratory droplets, physical contact and contact with surfaces as well as fomites. Isolation of patients in hospitals and quarantine of contacts in separate facilities are the mainstay of outbreak containment. This pandemic has brought forward various challenges to the hospital administrators, one of the most important being air-conditioning of hospitals in the time of this pandemic.